Learning Arabic For Children (Analysis of the Application of the Amtsilati Method to MIT Nurul Islam Semarang) - Moh Syakur; Ach. Hasymi Hashona (UIN Raden Mas Said Surakarta, 2022)
Arabic language learning for children in urban areas is far from ideal. Arabic in Indonesia is commonly identified with Pesantren and does not receive enough attention in urban areas. However, at MI Nurul Islam Semarang City, Arabic language learning for children gets enough attention from the founding father. Parents through committees often hold meetings to discuss children's learning achievements, including Arabic. One of the forms of attempt is to apply the Amtsilati method in Arabic language learning. The Amtsilati method is an alternative for Arabic teachers to make it easier for children to understand grammatical and word form in Arabic. To find out the information, researchers use field-based qualitative research methods with a descriptive approach. The required data is obtained by observation, interview, and documentation. The study found that the Amtsilati method is based on memorizing Arabic rules through song verses that are equipped with examples and adjusted to the level of children's abilities. Using this method, students who are able to learn Arabic well can even explain the arrangement and position of words in Arabic sentences. So that this finding becomes a recommendation for Arabic teachers so it can be used in Arabic learning, especially for learning Arabic grammar.